Neuroplasticity in F16 fighter jet pilots - Radstake, Wilhelmina E.; Jillings, Steven; Laureys, Steven; Demertzi, Athena; Sunaert, Stefan; Van Ombergen, Angelique; Wuyts, Floris L. (Frontiers in Physiology, 2023)
Exposure to altered g-levels causes unusual sensorimotor demands that must be dealt with by the brain. This study aimed to investigate whether fighter pilots, who are exposed to frequent g-level transitions and high g-levels, show differential functional characteristics compared to matched controls, indicative of neuroplasticity. We acquired resting-state functional magnetic resonance imaging data to assess brain functional connectivity (FC) changes with increasing flight experience in pilots and to assess differences in FC between pilots and controls. We performed whole-brain exploratory and region-of-interest (ROI) analyses, with the right parietal operculum 2 (OP2) and the right angular gyrus (AG) as ROIs. Our results show positive correlations with flight experience in the left inferior and right middle frontal gyri, and in the right temporal pole. Negative correlations were observed in primary sensorimotor regions. We found decreased whole-brain FC of the left inferior frontal gyrus in fighter pilots compared to controls and this cluster showed decreased FC with the medial superior frontal gyrus. FC increased between the right OP2 and the left visual cortex, and between the right left AG in pilots compared to controls. These findings suggest altered motor, vestibular, and multisensory processing in the brains of fighter pilots, possibly reflecting coping strategies to altered sensorimotor demands during flight. Altered FC in frontal areas may reflect adaptive cognitive strategies to cope with challenging conditions during flight. These findings provide novel insights into brain functional characteristics of fighter pilots, which may be of interest to humans traveling to space.